CONSTRUCTION DESIGN OF AN ASSISTING TOOL FOR IMMOBILIZATION IN THORAX AND ABDOMEN EXAMINATION ON PEDIATRIC PATIENTS - Arif Budiman; Rini Indrati; M. Choerul Anwar; Sudiyono Sudiyono; Jeffri Ardiyanto; Donny Kristanto Mulyantoro; Leny Latifah (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The main idea of designing an assisting tool for immobilization in pediatric thorax and abdomen examinations is that there are radiographer’ s difficulties while performing radiographs, especially pediatric thorax and abdomen. Aims: This study aims to design of appliance assist for immobilization thorax and abdomen examination on pediatric patients. Methods: This study was an exploratory experiment by designing, applying and testing the construction of an assisting tool for immobilization in thorax and abdomen examination on pediatric patients. The methods used in data collection were interview and observation. Function test results were analyzed based on the check list of the respondents regarding the feasibility of the tool. Results: an assisting tool for immobilization in thorax and abdomen examination on pediatric patients was designed in examination table-shaped made of basic materials such as acrylic, hollow steel and Eser steel plate. Function test on the work of the assisting tool was performed by 6 respondents who applied it to the patient. Based on the function test results, there was of 89,5% respondents who stated that the tool for immobilization in thorax and abdomen examination on pediatric patients could help the performance of the radiographer in positioning and reducing the patient’s movement and there was no artifact in the radiographs. Conclusion: Function test results showed that the tool design could reduce the movement of patients and may replace the function of others to resist the movement of the patient. An assisting tool for immobilization in thorax and abdomen examination on pediatric patients should be improved further especially in choosing the material used, so that the toll will be lighter and can better reduce the patient’s mobility and the size should consider the average height of the pediatric patients.